Replication timing properties of the human HPRT locus on active, inactive and reactivated X chromosomes - Subramanian, P S; Chinault, A C (Somatic cell and molecular genetics, 1997)
X chromosome inactivation is associated with a highly asynchronous pattern of DNA replication at most X-linked loci in females. We studied the human HPRT locus, which is subject to X inactivation and expressed from only the active homolog, with the goal of comparing replication properties between the active and inactive homologs in this region using a fluorescence in situ hybridization approach. We found that in normal female lymphoblasts this locus is replicated in a highly asynchronous manner across a broad, discrete 500-600 kb zone with earliest replication appearing at the gene coding sequence. This general timing profile is maintained in normal male lymphoblasts, as well as in hamster x human hybrid cells containing the active human X chromosome. However, the inactive human X chromosome in the hamster cell background does not appear to function in a fully equivalent manner to the normal inactive X chromosome in female cells. Furthermore, reactivation of the inactive human X chromosome in a hamster x human hybrid system by 5-azacytidine treatment and HAT selection restores early replication at the HPRT gene itself, but does not change the overall domain behavior.